The Greek testament ; v.2 with English notes, critical, philological and exegetical especially adapted to the use of theological students, and ministries. - Bloomfield, S.T. (London, UK Longman, Brown, Green, and Longmans, 1855)
Contents : v. 2 : Romans-Revelation. Includes bibliographical references and index for both vols.
Keywords: Bible. N.T. Greek -- commentaries